Synergizing Virtual Labs and Project-Based Learning: Innovating Modern Physics Education with Interactive Modules - Sri Purwaningsih; Rahma Dani; Edi Yuversa (STAI Hubbulwathan Duri, 2024)
Inadequate learning facilities in the Department of Physics Education contribute to the lack of student involvement during modern physics lectures. The learning approach primarily revolves around lecturers, and the effectiveness of Zoom for online learning among students is limited. Therefore, the aim of this research is to design a virtual lab-based learning module integrated with project-based learning to enhance students' conceptual understanding. This research employed a development method with the 4D model. The research subjects included two expert validators to assess the product's feasibility, five students for small-group trials, and 22 students for effectiveness trials. Validators were given questionnaires to evaluate the module's feasibility, while students were given questionnaires to gauge their responses to the module. To evaluate the efficacy of the module, students underwent pre-tests and post-tests consisting of 5 essay questions. Analysis encompassed consolidating validation outcomes and student feedback. Concurrently, test results were assessed using N-Gain tests and paired t-tests. The research outcomes indicated that the integration of virtual lab-based learning with PBL in modern physics was both feasible and effective in enhancing students' conceptual comprehension.